PHYSIOTHERAPY MANAGEMENT IN PLANTAR FASCITIS CASES: CASE REPORT - Nikmah, Rakhma Nur Fitratun; Wahyuni, Wahyuni; Yunanto, Sri (JTH: Journal of Technology and Health, 2025)
This study aimed to evaluate the effects of a combined physiotherapy intervention—ultrasound, TENS, stretching, and strengthening exercises—on pain, joint mobility, muscle strength, and functional activity in a patient with plantar fasciitis caused by a calcaneal spur. A case study was conducted involving a 58-year-old female patient who underwent three physiotherapy sessions over two weeks. The interventions included ultrasound (3 MHz frequency, 5 minutes, twice a week), TENS (continuous mode, 15 minutes, intensity per patient tolerance), stretching (calf raises and towel stretches, 2 sets of 10 repetitions), and ankle strengthening exercises using a theraband (8-second holds for 8 minutes). Pre- and post-intervention assessments used the Numeric Rating Scale (NRS), goniometer, Manual Muscle Testing (MMT), and the Foot and Ankle Disability Index (FADI). The results showed reductions in pain (rest: 5–2; pressure: 5–3; movement: 7–5), improved joint mobility, and an increase in FADI score from 51 to 57, although no significant changes were observed in muscle strength. The novelty of this study lies in the integration of weekly functional assessment (FADI) into an evidence-based multimodal physiotherapy protocol applicable in resource-limited clinical settings.